(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This paper seeks to reflect on altered states of consciousness, taking as a reference the research shared by the Arkhétypos Group (Brazil) and the Bimphadi Group (Angola) at the Bimphadi International Otyoto that took place in Angola in 2022. In this sense, the discussion stems from an initial reflection published in 2021 (Oliveira Neto; Haderchpek) and seeks to broaden the analytical framework by researching groups of other nationalities. The empirical research was structured based on participant observation. The preliminary results allow us to conclude that the ritualistic practices developed by the Angolan actors facilitate their access to altered states of consciousness.